A qualitative study on experiences of persons with schizophrenia in oral-health-related quality of life - DENIS,Frédéric (2021)
Abstract Our study aimed to explore the views and experiences in oral health and oral-health-related quality of life (OHRQoL) of persons with schizophrenia (PWS) in order to expand the understanding of the factors that either limit or facilitate their healthcare pathway, which can ultimately optimize their oral health and/or OHRQoL. A qualitative study was conducted in France in the Côte d’Or department (530 000 in habitants) centered on PWS’s perceived meanings regarding oral health or OHRQoL, and semi-structured individual interviews were used. A conventional content analysis approach was chosen in order to highlight unrevealed themes. A sample of 20 PWS (12 males; 8 females) with a median age was 45.8 (± 9.5) were recruited to assess views and experiences regarding OHRQoL, which were focused on three dimensions: an individual dimension related to experience of “oral symptoms”, a second dimension related to experience of “stress and its management”, and a third related to “Autonomy dimension in oral health”. We showed that PWS clearly expressed their mental representations of oral health and OHRQoL. This study supports that PWS were able to define their needs and had the ability to discuss their oral health and OHRQoL. These finding could be used to support specific interventions for this population to better manage the negative impact of antipsychotics and help them to consult dentists on a regular basis.